The Mononuclear Phagocytic System. Generation of Diversity - Gordon, Siamon; Plüddemann, Annette (Frontiers in Immunology, 2019)
We are living through an unprecedented accumulation of data on gene expression by macrophages, reflecting their origin, distribution and localisation within all organs of the body. While the extensive heterogeneity of the cells of the mononuclear phagocyte system is evident, the functional significance of their diversity remains incomplete, nor is the mechanism of diversification understood.In this essay we review some of the implications of what we know, and draw attention to issues to be clarified in further research, taking advantage of the powerful genetic, cellular and molecular tools now available.Our thesis is that macrophage specialisation and functions go far beyond immunobiology, while remaining an essential contributor to innate as well as adaptive immunity.